2021
DOI: 10.1039/d1ob01208h
|View full text |Cite
|
Sign up to set email alerts
|

Electrooxidative double C–H/C–H coupling of phenols with 3-phenylbenzothiophenes: facile access to benzothiophene derivatives

Abstract: An efficient electrooxidative double C-H/C-H coupling of phenols with 3-phenylbenzothiophene has been developed under external oxidant- and catalyst-free conditions. This strategy could enable the highly tunable access to benzothiophene derivatives...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Then, a radical coupling between these two intermediates occurred and, aer deprotonation, benzothiophene derivative products were obtained (Scheme 91). 232 1.6. Acylation Acylation reactions of phenolic compounds are widely used in the synthesis of ne chemicals such as avours (i.e.…”
Section: Arylationmentioning
confidence: 99%
See 2 more Smart Citations
“…Then, a radical coupling between these two intermediates occurred and, aer deprotonation, benzothiophene derivative products were obtained (Scheme 91). 232 1.6. Acylation Acylation reactions of phenolic compounds are widely used in the synthesis of ne chemicals such as avours (i.e.…”
Section: Arylationmentioning
confidence: 99%
“…[227][228][229] Scheme 91 Electro-oxidative coupling of phenols and 3-phenylbenzothiophenes. 232 S. R. Waldvogel et al in 2019 reported a highly para-selective electrochemical protocol for the anodic dehydrogenative 2,5and 2,6-substituted phenol-phenol cross-coupling and homocoupling. This synthetic strategy gave access to a broad range of non-symmetric and symmetric 4,4 0 -biphenols under mild reaction conditions.…”
Section: Arylationmentioning
confidence: 99%
See 1 more Smart Citation
“…11 12 Consequently, molecules containing these motifs have received considerable attention in organic synthesis and drug discovery, featuring prominently across various drug candidates, such as antibiotics, anticancer agents, and neuropharmacological compounds. 13 14 15…”
Section: Table 1 Optimization Of Reaction Conditions ...mentioning
confidence: 99%
“…11,12 Consequently, molecules containing these motifs have received considerable attention in organic synthesis and drug discovery, featuring prominently across various drug candidates, such as antibiotics, anticancer agents, and neuropharmacological compounds. [13][14][15] o-Dihaloarenes as potential electrophiles readily undergo simultaneous or sequential difunctionalization through transition-metal-catalyzed cross-coupling reactions, making them attractive and versatile building blocks for the rapid construction of complex heterocycles. 14,[16][17][18][19][20][21] For example, Barluenga, Valdés, and co-workers discovered a Pdcatalyzed regioselective domino reaction of o-dihaloarenes with imines to afford structurally diverse indoles.…”
mentioning
confidence: 99%